A GIS Based Unsteady Network Model and System Applications for Intelligent Mine Ventilation - Hui. Liu; Shanjun Mao; Mei. Li; Pingyang Lyu (Discrete Dynamics in Nature and Society)
With the development of state-of-the-art technology, such as the artificial intelligence and the Internet of Things, the construction of “intelligent mine” is being vigorously promoted, where the intelligent mine ventilation is one of the primary concerns that provides the efficient guarantee for safety production in the underground coal mine system. This study aims to integrate the geographical information system (GIS) and the unsteady ventilation network model together, to provide location based information and online real-time support for the decision-making system. Firstly, a GIS based unsteady network model is proposed, and its algorithm steps are brought out. Secondly, a prototype web system, named 3D VentCloud, is designed and developed based on the front and end technique, which effectively integrates the proposed algorithms. Thirdly, the model is validated, and the system is applied to a real coal mine for ventilation solution, which demonstrates that the model is reasonable and practical. The online simulation system is efficient in providing real-time support. The study is potential and is expected to guide the real-time coal mine safety production.